2020
DOI: 10.1001/jamainternmed.2019.3833
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Subspecialty Choices of Men and Women in Internal Medicine From 1991 to 2016

Abstract: Women have been enrolling in medical schools in increasing numbers in the last few decades, reaching 50.7% of matriculants in 2017. 1 Of 25 749 internal medicine residents in 2017, 42.4% were women. 2 We examined changes in the internal medicine subspecialty choices of women and men from 1991 to 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 4 publications
0
37
1
Order By: Relevance
“…Cardiology is not a diverse profession, with underrepresentation of women and Black, Latinx, and other groups. 2 The American College of Cardiology, American Heart Association, and other societies have recognized this as a problem for the profession that limits access to talent and impacts the care of an increasingly diverse patient population. 9 The goal of a more diverse profession can be accomplished only by attracting a broader range of trainees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiology is not a diverse profession, with underrepresentation of women and Black, Latinx, and other groups. 2 The American College of Cardiology, American Heart Association, and other societies have recognized this as a problem for the profession that limits access to talent and impacts the care of an increasingly diverse patient population. 9 The goal of a more diverse profession can be accomplished only by attracting a broader range of trainees.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of women and underrepresented racial and ethnic groups (UREGs) (defined as Black, Hispanic, Latinx, or Native American) 1 in cardiology training programs do not reflect population demographic characteristics. Although the percentage of women internal medicine residents increased from 30.2% to 43.2% between 1991 and 2016, 2 only 21.3% of cardiovascular fellows in 2016 were women, in stark contrast to 76.9% of geriatrics and 42.9% of hematology-oncology fellows. This may be due to negative perceptions of cardiology among internal medicine residents, 3 who highlight adverse job conditions, interference with family life, and a lack of existing diverse faculty.…”
Section: Introductionmentioning
confidence: 96%
“…Also, with faculty data, the comparisons made in this study are based on faculty department and not specialty; for IM, this approach does not allow for the identification of the actual practice specialties of faculty members. 20 Although we did not have these data available at the faculty level, 2 recently published articles 52 , 53 examined trends by sex and race/ethnicity for IM residents and IM subspecialty fellows. Santhosh and Babik 52 found that although the overall total of IM residents and IM subspecialty fellows increased from 2006 to 2018 (from 21 855 to 26 228 residents and 8144 to 10 578 fellows), the proportion of URM IM residents was unchanged (2688 [12.3%; 95% CI, 11.9%-12.7%] to 3599 [13.7%; 95% CI, 13.3%-14.1%]; P = .28) but increased to various extents for all subspecialty fellowships.…”
Section: Discussionmentioning
confidence: 99%
“…Santhosh and Babik 52 found that although the overall total of IM residents and IM subspecialty fellows increased from 2006 to 2018 (from 21 855 to 26 228 residents and 8144 to 10 578 fellows), the proportion of URM IM residents was unchanged (2688 [12.3%; 95% CI, 11.9%-12.7%] to 3599 [13.7%; 95% CI, 13.3%-14.1%]; P = .28) but increased to various extents for all subspecialty fellowships. Stone et al 53 examined trends related to sex and found that from 1991 to 2016 the absolute number and the proportion of female IM residents increased substantially (5602 [30.2%] to 10223 [43.2%]), but the proportion of female IM subspecialty fellows decreased during this same period (33.3% in 1991 and 23.6% in 2016). In addition, given the cross-sectional nature of these data and a lack of information regarding faculty and student experiences, we cannot infer causality from any of the results presented.…”
Section: Discussionmentioning
confidence: 99%
“…The outlook for attracting more women into cardiology is also grim. Although the proportion of fellows who were women doubled from 10.1% in 1991 to 21.3% in 2016, even the more recent “improved” number is lower than that for every other subspecialty in medicine back in 1991 except gastrointestinal and pulmonary/critical care ( 4 ). In 2019, the American College of Graduate Medical Education included work force diversity in its program evaluation requirements, a wakeup call for cardiology ( 5 ).…”
mentioning
confidence: 99%